Penggunaan Teknologi Unity Dalam Pembuatan Gim Edukasi Sejarah: Pertempuran 10 November 1945 - Achmad Zahrul Ali Zadan; Pratama Wirya Atmaja; Andreas Nugroho Sihananto (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The development of technology in learning has opened up new opportunities to improve historical understanding through innovative approaches. In this context, this research focuses on the use of Unity technology in the development of an educational game that explores the events of the Battle of November 10, 1945 in Surabaya. This research aims to design and implement an educational game that is interactive and deepens understanding of the historical event. Researchers utilized the Unity development platform to create a near-native environment and provide a fun learning experience. The method used is Interactive Digital Narratives (IDN). The result of this research is an educational narrative-based game the history of the Battle of November 10, 1945.